TANGGUNG JAWAB NOTARIS TERHADAP KEKELIRUAN PEMBUATAN AKTA WASIAT YANG DIDASARKAN PADA RESUME RAPAT KELUARGA PEWARIS - Febianto, Jacelyn; Saleh, Putu Samawati; Sagita, Anna (Lex Jurnalica, 2025)
AbstractNotary as a public official is authorised to make a will deed by prioritising the principle of prudence. Supreme Court Decision Number 1968 K/Pdt/2018 stated that the notarial deed of will made based on the family meeting resume was cancelled. The purpose of this research is to know, understand, and analyse the position of the testamentary deed made based on the testator's family meeting resume and the notary's responsibility for the testamentary deed. This research is a normative research with statutory, conceptual and case approaches. The research legal material consists of primary and secondary, using library legal material collection techniques, qualitative research legal material analysis techniques, and inductive inference techniques. The results showed that the position of the deed of will made based on the resume of the testator's family meeting causes the deed to be null and void because it contains unlawful acts as Article 1365 of the Civil Code committed by the notary, namely violating the provisions of Articles 875, 944 of the Civil Code and 40 paragraph (2). Notaries can be held civilly, administratively and criminally liable for their negligence. Facts that show that notaries do not use the precautionary principle in carrying out their duties have an impact on the attendees and heirs. Strict action not only provides administrative sanctions but fines or compensation is an effort to minimise the negligence of notaries in carrying out their duties, in addition to providing protection and certainty of the fulfilment of the rights of the attendees or heirs.